Spinal and Bulbar Muscular Atrophy – Genetic Causes, Clinical Presentation and Treatment Perspectives - Emerla, Sara; Małek, Natalia; Karłowicz, Konrad; Brożyna, Aleksandra; Kwiatkowska, Anita; Bydliński, Arkadiusz; Hermanowska, Maria; Lubomirska, Julia; Figurowska, Patrycja; Ciulkiewicz, Łukasz (Journal of Education, Health and Sport, 2024)
Introduction and Purpose: Spinal bulbar muscular atrophy (SBMA), also known as Kennedy's disease, is a rare genetic disorder characterized by progressive muscle weakness and atrophy. The purpose of this review is to provide a comprehensive understanding of SBMA, including its pathophysiology, clinical presentation, diagnostic tools, and therapeutic approaches. By examining the latest research findings, we aim to highlight the challenges inherent in managing SBMA. Material and method: For this review, we performed searches across multiple databases, including PubMed, Elsevier, Medline, and Google Scholar. Description of the State of Knowledge: SBMA arises from mutations in the androgen receptor (AR) gene, leading to the accumulation of toxic proteins and subsequent neurodegeneration. Clinical manifestations primarily involve muscle weakness, tremors, and difficulties with speech and swallowing, with symptoms typically appearing in mid-life. While no treatment currently modifies disease progression, symptomatic management and supportive care play crucial roles in enhancing quality of life for affected individuals. Recent research has focused on understanding the underlying mechanisms of SBMA and developing targeted therapies to address them. However, challenges remain in translating these findings into effective treatments. Conclusions: SBMA represents a complex and challenging neurodegenerative disorder with significant implications for affected individuals and their families. While our understanding of SBMA has advanced in recent years, much remains to be elucidated regarding its pathophysiology and optimal management strategies. Continued research efforts are essential to develop novel therapeutic interventions that can effectively target the underlying mechanisms of SBMA and improve outcomes for patients.